2012
DOI: 10.1039/c2ce25271f
|View full text |Cite
|
Sign up to set email alerts
|

Topotactic transformation of single-crystalline TiOF2 nanocubes to ordered arranged 3D hierarchical TiO2 nanoboxes

Abstract: 3D hierarchical TiO 2 nanoboxes, enclosed by six ordered arranged TiO 2 nanorod arrays, were prepared via a templateengaged topotactic transformation process from TiOF 2 nanocubes. The lattice matching between TiOF 2 and anatase TiO 2 was regarded as the key for the preferential growth and ordered arrangement of the TiO 2 nanorods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…In Figure 2a,b, TiOF2 crystals displayed a mixture of the cubic image which is accords with the cubic image in [7][8][9][10][11][12][13][14][15][16][17][18]. Each individual particle crystal is about 50-300 nm and tends to aggregate, forming larger particles while-in Figure 2c,d-the NaOH-modified TiOF2 displayed a more complex network shape with network units in about 100 nm.…”
Section: Phase Structures and Morphologymentioning
confidence: 49%
See 2 more Smart Citations
“…In Figure 2a,b, TiOF2 crystals displayed a mixture of the cubic image which is accords with the cubic image in [7][8][9][10][11][12][13][14][15][16][17][18]. Each individual particle crystal is about 50-300 nm and tends to aggregate, forming larger particles while-in Figure 2c,d-the NaOH-modified TiOF2 displayed a more complex network shape with network units in about 100 nm.…”
Section: Phase Structures and Morphologymentioning
confidence: 49%
“…Only a few studies focused on the photocatalytic activity of TiOF2 have been reported [7][8][9]. As usual, TiOF2 nanoparticles were synthesized via hydrothermal [10,[14][15][16][17][18] and solvothermal [7,11,12] methods from titanium (IV) isopropoxide (TIP), and have a cubic shape [7][8][9][10][11][12][13][14][15][16][17][18]. The size of TiOF2 nanocubes could be affected by alcoholysis time, alcohol kind, solvothermal temperature, different H2O production rate and amount [7,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,13] Attributed to ac ovalent interaction between F and Ti,T iOF 2 was proposed as an F-dopant source to obtain av isible-light photocatalyst for dye degradation. [16] Oner emaining question focuses on how to obtain the n-type F-doping in TMCs with higher contents of Fd uring the topotactic transformation, while understandingt he mechanismso ff ormation. [15] It wasd iscovered that the stability of the reactive (0 01)f acet and crystallization can be improved after the Fspecies was introduced from TiOF 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[15] It wasd iscovered that the stability of the reactive (0 01)f acet and crystallization can be improved after the Fspecies was introduced from TiOF 2 . [16] Oner emaining question focuses on how to obtain the n-type F-doping in TMCs with higher contents of Fd uring the topotactic transformation, while understandingt he mechanismso ff ormation. The details of the oriented transformation of TMCs and its compatibility with n-type F-doping are not yet reported.…”
Section: Introductionmentioning
confidence: 99%